1984
DOI: 10.1097/00000658-198411000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Treatment of the Acute Scrotum in Children and Adolescents

Abstract: Diagnosing acute scrotal pain and swelling in children and adolescents is urgent and often difficult. A review of 395 boys hospitalized with acute scrotal pain and/or swelling shows that a useful approach is to divide these patients into four groups--those with intermittent but recurrent episodes of pain, those with pathognomonic physical findings, those with definite epididymitis, and a remaining group with nonspecific swelling and tenderness. Five per cent of boys in this series presented with recurring epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
3

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 17 publications
5
63
0
3
Order By: Relevance
“…While cold weather was implicated in at least one review [12], an increase in the incidence of torsions in winter was not found in the Al-Jahra series. Most reviews of torsions indicated that testicular appendages are more often involved than the testes, and that the left scrotal contents are more often involved than the right ones [8,[13][14][15].These findings were also reproduced in this series.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…While cold weather was implicated in at least one review [12], an increase in the incidence of torsions in winter was not found in the Al-Jahra series. Most reviews of torsions indicated that testicular appendages are more often involved than the testes, and that the left scrotal contents are more often involved than the right ones [8,[13][14][15].These findings were also reproduced in this series.…”
Section: Resultssupporting
confidence: 66%
“…Intrascrotal torsions are common in transpubertal and postpubertal age due to the increase in testicular mass [7][8][9]. Vigorous exercise, local trauma, a powerful cremasteric reflex and sexual excitement are possible precipitating factors of TT [2,10].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with scrotal symptoms such as pain, swelling, and redness, it is important to differentiate testicular diseases from extratesticular scrotal disorders (1,2). Testicular diseases, including testicular torsion, malignant testicular tumor, and traumatic damage, require surgical exploration, whereas other testicular diseases and extratesticular scrotal disorders such as acute epididymo-orchitis, appendiceal torsion, and so on can be treated by means of conservative therapy (1)(2)(3).…”
Section: Methodsmentioning
confidence: 99%
“…The presenting symptom is unilateral testicular pain. Testicular torsion is the main differential diagnosis and should be considered in all cases, since delay in emergency surgery will adversely effect prognosis 1,2 . Differential diagnosis is based on symptoms at presentation (especially onset, duration and severity of pain), microbiological assessment and, if indicated, colour Doppler ultrasound 3 .…”
Section: Introductionmentioning
confidence: 99%